Electric field effect on exchange interaction in ultrathin Co films with ionic liquids. (11th May 2018) - Ishibashi, Mio; Yamada, Kihiro T.; Shiota, Yoichi; Ando, Fuyuki; Koyama, Tomohiro; Kakizakai, Haruka; Mizuno, Hayato; Miwa, Kazumoto; Ono, Shimpei; Moriyama, Takahiro; Chiba, Daichi; Ono, Teruo
Abstract: Electric-field modulations of magnetic properties have been extensively studied not only for practical applications but also for fundamental interest. In this study, we investigated the electric field effect on the exchange interaction in ultrathin Co films with ionic liquids. The exchange coupling J was characterized from the direct magnetization measurement as a function of temperature using Pt/ultrathin Co/MgO structures. The trend of the electric field effect on J is in good agreement with that of the theoretical prediction, and a large change in J by applying a gate voltage was observed by forming an electric double layer using ionic liquids.